2020
DOI: 10.1007/s41999-019-00260-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological approaches in the prevention of delirium

Abstract: Aim To summarize the evidence concerning the efficacy of non-pharmacological interventions in delirium prevention in older adults admitted to hospital. Findings The evidence for non-pharmacological, multi-component interventions is sufficiently robust for clinical practice recommendations to be formulated. However, no conclusive effects have been demonstrated on outcomes more distal to delirium occurrence and for single-component interventions. Message Pragmatic studies should be conducted, aimed at investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Preoperative stratification of patients based on estimated risk for postoperative delirium could identify those patients expected to benefit most from preventive measures. Although there is no conclusive evidence that different drugs are effective in preventing delirium,39 the evidence for non-pharmacological multicomponent interventions is considered sufficiently robust for clinical practice recommendations in elderly non-ICU patients 6. In healthcare institutions, applying multicomponent non-pharmacological measures to all patients would result in a high burden on scarce human and material resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preoperative stratification of patients based on estimated risk for postoperative delirium could identify those patients expected to benefit most from preventive measures. Although there is no conclusive evidence that different drugs are effective in preventing delirium,39 the evidence for non-pharmacological multicomponent interventions is considered sufficiently robust for clinical practice recommendations in elderly non-ICU patients 6. In healthcare institutions, applying multicomponent non-pharmacological measures to all patients would result in a high burden on scarce human and material resources.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no conclusive evidence that different drugs are effective in preventing delirium, 39 the evidence for non-pharmacological multicomponent interventions is considered sufficiently robust for clinical practice recommendations in elderly non-ICU patients. 6 In healthcare institutions, applying multicomponent non-pharmacological measures to all patients would result in a high burden on scarce human and material resources. The labour-intensive and costly nature of multicomponent interventions requires appropriate selection of patients who are expected to benefit most from such interventions or for whom certain interventions could be omitted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature that included broader study types examining nonpharmacological approaches in the prevention of delirium concluded that evidence for multicomponent interventions is sufficiently robust for clinical practice recommendations to be formulated [42]. However, no conclusive outcome effects have been demonstrated for single-component interventions.…”
Section: Delirium Risk Reduction/preventionmentioning
confidence: 99%